1981
DOI: 10.1007/bf00262340
|View full text |Cite
|
Sign up to set email alerts
|

Changes in toxic and antitumor properties of ftorafur by induction or inhibition of the microsomal enzymes activity

Abstract: The inducers of microsomal drug-metabolizing enzymes phenobarbital (PB) and 20-methylcholanthrene (MC) inhibited the lethargic effect of high doses of ftorafur in C57BL/6j mice, but stimulated the animal mortality at days 4-8 after the drug administration. The opposite effect has been obtained by the combination of ftorafur with the inhibitor of the microsomal enzymes SKF 525A. Animal pretreatment with PB or with PB + MC markedly enhanced the antineoplastic activity of ftorafur in Rauscher leukemia-, leukemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
1993
1993

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…However, these data are not confirmed by experimental studies which demonstrated cross-resistance of TG and 5-FU in mice bearing L1210 lymphocytic leukaemia (Garibjarian et al, 1976). Initial pharmacological studies showed that TG is a pro-drug of 5-FU for it is slowly metabolised in the liver by microsomal enzymes to 5-FU (Belitsky et al, 1981). 5-FU is in turn slowly released into the systemic circulation where it reaches detectable levels for a prolonged period of time (Garibjanian et al, 1976;Benvenuto et al, 1978;Schilcher et al, 1983).…”
Section: Italymentioning
confidence: 99%
“…However, these data are not confirmed by experimental studies which demonstrated cross-resistance of TG and 5-FU in mice bearing L1210 lymphocytic leukaemia (Garibjarian et al, 1976). Initial pharmacological studies showed that TG is a pro-drug of 5-FU for it is slowly metabolised in the liver by microsomal enzymes to 5-FU (Belitsky et al, 1981). 5-FU is in turn slowly released into the systemic circulation where it reaches detectable levels for a prolonged period of time (Garibjanian et al, 1976;Benvenuto et al, 1978;Schilcher et al, 1983).…”
Section: Italymentioning
confidence: 99%
“…Many efforts have been made to increase the antitumor activity of FT by obtaining a high plasma concen tration of 5-FU (6,7). In the previous paper (8), we reported that the plasma concen trations of both FT and 5-FU increased after administration of FT (500 mg/kg, p.o.)…”
Section: (Tetrahydro 2 Furanyl) 5 Fluorouracil (Ft)mentioning
confidence: 99%